166k views
4 votes
Need help badly don’t have answer to this problem.

Need help badly don’t have answer to this problem.-example-1
User Silwest
by
6.3k points

2 Answers

1 vote
You can use the cosine function for this.

cos 45 = x/6√2
6√2 (cos 45) = x
8.485 (cos 45) = x
5.99 = x
6 ≈ x

The answer is D

Hope this helps :)
User Rihards
by
5.4k points
5 votes
there are a couple of ways to tackle this one, using the 45-45-90 rule or just using the pythagorean theore, let's use the pythagorean theorem.

the angle at A is 45°, and its opposite side is BC, the angle at C is 45° as well, and its opposite side is AB, well, the angles are the same, thus BC = AB.

hmmm le'ts call hmmm ohh hmmm say z, thus BC = AB = z.


\bf \textit{using the pythagorean theorem} \\\\ c^2=a^2+b^2 \implies (6√(2))^2=z^2+z^2 \qquad \begin{cases} c=\stackrel{6√(2)}{hypotenuse}\\ a=\stackrel{z}{adjacent}\\ b=\stackrel{z}{opposite}\\ \end{cases}\\\\\\ 6^2(√(2))^2=2z^2\implies 36(2)=2z^2\implies \cfrac{36(2)}{2}=z^2\implies 36=z^2 \\\\\\ √(36)=z\implies 6=z
User Mickael
by
6.1k points